Modification of High-Quality Porous Concrete Asphalt with Local Materials as an Alternative to Flexible Pavement - Irawati Irawati; Ilanka Cahya Dewi (Universitas Tribhuwana Tunggadewi Malang, 2024)
Environmental issues and a lack of attention to open space as rainwater catchment areas cause flooding problems in urban areas. Constructing environmentally friendly roads with permeable capabilities is one way to prevent waterlogging along the road in the rainy season. This study evaluated the type of porous asphalt concrete called Open Graded Friction Course specification Japanese standard. This study modified porous asphalt concrete using bamboo fiber and hydrated lime. Stability testing is conducted by the Marshall method, and the volumetric mixture is analyzed. Stability testing is carried out by the Marshall method and analysis of the volumetry of the mixture is carried out. The results showed that adding bamboo fiber and hydrated lime increased stability and maintained the porosity of the porous asphalt concrete.